WEBINAR NASIONAL TUBERKULOSIS PADA MASA PANDEMI COVID -19 DI LINGKUNGAN MASYARAKAT - Khairul Bariyah; Khoirul Rista Abidin; Luluk Deka Fatmawati; Ainun Sa'adah (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Tuberculosis is a direct infectious disease caused by Tuberculosis bacteria (Microbacterium Tuberculosis). The response to the Covid-19 pandemic requires adjustments to other health program services, including TB services that are run at health care facilities. Indonesia is the country with the most Covid-19 cases in Southeast Asia. Where people with Covid-19 and TB can show the same symptoms as cough, fever, and difficulty breathing. Both of these diseases attack mainly the lungs and both biological agents are transmitted through close contact or physical contact. Objective: to determine the relationship between science and tuberculosis prevention during the Covid-19 pandemic in the community. Methods: questionnaires on data collection techniques in quantitative research as community service and the role of health webinar participants in science and prevention of tuberculosis during the Covid-19 pandemic in the community. The media used is the website of the Pontianak Aisyiyah Polytechnic campus (Polita). This community service was carried out on February 4, 2021. Results: The number of participants who registered for the webinar was 1,498 people, where participants in the science category were in the very good category on tuberculosis and prevention 98.7% - 79.6%, good category on transmission with family and environment 65.2%-59.2%, and the lowest method of TB examination is 40.9%. Conclusion: This study involved webinar participants in knowledge and prevention of TB, the highest was 98.7% and the lowest was the method of TB examination, 40.9%, which was carried out in the laboratory. This National Health Webinar is a solution in handling knowledge and preventing Tuberculosis during the Covid-19 pandemic in Indonesian society.